Gambaran Tingkat Pengetahuan Kader TB di Kabupaten Batang - Habibillah, Annis Syahri; Martini, Martini; Yuliawati, Sri; Saraswati, Lintang Dian; Hestiningsih, Retno (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Background: Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Health cadres are one of the important elements that contribute to community empowerment in achieving TB detection. The ability of cadres to mobilize the community is an indicator of success in conveying health messages to the community. Knowledgeable TB cadres are very helpful in controlling pulmonary tuberculosis cases. This study aims to describe the description of the level of knowledge of TB cadres in Batang Regency.Methods: This research is a descriptive observational study using a cross sectional research design. The sample size in this study was 126 respondents using a total sampling technique. The research respondents were all TB cadres who were in the working area of the Batang District Health Office. Interview using a questionnaire. Interview data were processed using the frequency distribution test and descriptive analysis using the SPSS program.Result: Based on the research results, it can be said that most of the cadres are 36-45 years old with an average age of 40.6 years. The majority of cadres have good knowledge (60.3%), and 39.7% of cadres have less knowledge.Conclusion: Most of the cadres are 36-45 years old with the majority of TB cadres having a good level of knowledge. Keywords: Tuberculosis, TB cadres, knowledge, level